Інформаційне забезпечення діяльності територіальної самоврядної громади в соціальних мережах - Химиця, Наталія; Кіпень, Надія (Видавництво Львівської політехніки, 2015)
This article reveals the essence of information support community in social networks, describes the meaning of "self-governing community". Also talking about the need to implement information technology in the activities of local selfgovernment. In this paper examines the main priorities the creation of these communities and their benefits. Moreover, given and disadvantages to consider when using this type of information provision.
Keywords: самоврядна територіальна громада; інформаційна діяльність; Інтернет; соціальні мережі